4-Vinylbenzene Boronic Acid-Hydroxy Apatite/Polyvinyl Alcohol Based Nanofiber Scaffold Synthesized by UV-Activated Reactive Electrospinning - KAHRAMAN, MEMET VEZİR (TAYLOR & FRANCIS AS, 2015)
In this study, we prepared photo-crosslinked modified HAP (hydroxy apatite)/polyvinyl alcohol (PVA) composite nanofiber scaffold for cell growth applications. HAP was synthesized and then modified with 4-vinylbenzene boronic acid (VBBA) to obtain 4-VBBA-HAP. By means of the simultaneous UV electrospinning technique 4-VBBA-HAP/PVA composite was obtained. The structure and morphology of electrospun membranes were investigated by scanning electron microscopy) and Fourier transform infrared spectroscopy technique. Nanofibers were treated with collagen solution via the spraying method. For the cell culture applications ECV304 and SAOS cells were seeded on the chosen electrospun fibrous scaffolds. [GRAPHICS] .
Keywords: Cell culture; ECV; electrospinning; HAP; nanofiber; SAOS; UV curing